Subjective Cognitive Decline and Related Cognitive Deficits - Si, Tong; Xing, Guoqiang; Han, Ying (Frontiers in Neurology, 2020)
Since late stage dementia including Alzheimer's disease(AD)cannot be reversed by any available drugs, there is increasing research interests on the preclinical stageof AD i.e.subjective cognitive decline(SCD). SCD ischaracterized withself-perceptive cognitive decline but difficult to detect using objective tests. At SCD stage, the cognitive deficits could be more easily reversed compared to that ofmild cognitive impairment (MCI) and ADonly if accurate diagnosis of SCD and early intervention can be developed.In this paper, we briefly review the recent progress ofSCD research including current assessment tools, biomarkers, neuroimaging, intervention and expected prognosis and the potential relevance totraumatic brain injury (TBI)-induced cognitive deficits.